Text Encoding Using Cipher Block Chaining Algorithm - Santana Sinurat; Maranatha Pasaribu (SEAN Institute, 2021)
. Data confidentiality and security are critical in data communication, both for the purpose of shared security, and for individual privacy. Computer users who want their data unknown to unauthorized parties are always trying to work out how to secure the information that will be communicated or that will be stored. Protection against data confidentiality is increasing, one way is by applying cryptographic science. Cipher Block Chaining (CBC), this mode is a feedback mechanism on a block, and in this case the result of the previous block encryption is feedback into the current block encryption. The trick is to block the current plaintext in XOR first with the ciphertext block of the previous encryption result, then the result of this XOR-ing goes into the encryption function. With CBC mode, each ciphertext block is calculated not only on its plaintext block but also on the entire previous plaintext block. The author tries to co-create a text encoding to secure the data with the Cipher Block Chaining (CBC) cryptographic method.